2021
DOI: 10.1371/journal.pone.0252144
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 serum levels are related to insulin resistance, metabolic changes and obesity in Mexican people living with HIV (PLWH)

Abstract: Background Antiretroviral therapy has significantly improved prognosis in treatment against HIV infection, however, prolonged exposure is associated to cardiovascular diseases, lipodystrophy, type 2 diabetes, insulin resistance, metabolic alteration, as obesity which includes the accumulation of oxidative stress in adipose tissue. FGF21 is a peptide hormone that is known to regulate glucose and lipid metabolism. FGF21 is expressed and secreted primarily in the liver and adipose tissue, promoting oxidation of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Consistent with the results observed in our study, others have also reported increased FGF21 levels in individuals with obesity and a positive correlation with adiposity, insulin, and triglycerides [37]. This paradox between the beneficial effects of FGF21 on metabolism and the observed augmented circulating levels in human adults with overweight and obesity might be explained by an "FGF21-resistant" state in these individuals [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the results observed in our study, others have also reported increased FGF21 levels in individuals with obesity and a positive correlation with adiposity, insulin, and triglycerides [37]. This paradox between the beneficial effects of FGF21 on metabolism and the observed augmented circulating levels in human adults with overweight and obesity might be explained by an "FGF21-resistant" state in these individuals [38].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it might seem paradoxical that we observed a positive association between the plasma levels of FGF21 during the warm period and several markers of adiposity and cardiometabolic risk, including BMI, WC, visceral adipose tissue mass, insulin, HOMA‐IR, and cholesterol. Consistent with the results observed in our study, others have also reported increased FGF21 levels in individuals with obesity and a positive correlation with adiposity, insulin, and triglycerides [37]. This paradox between the beneficial effects of FGF21 on metabolism and the observed augmented circulating levels in human adults with overweight and obesity might be explained by an “FGF21‐resistant” state in these individuals [38].…”
Section: Discussionsupporting
confidence: 91%
“…As discussed above, conditions associated with overfeeding, including obesity, are also associated with increased systemic FGF21 levels. This has been shown consistently in humans and rodents fed a HFD, diets high in carbohydrates, and ketogenic diets (3,20,72,73,128), as well as humans with obesity (26)(27)(28)76) and in humans that have been acutely overfed (164). In many of these studies, mRNA and protein expression of FGF21 have consistently been shown to be increased in WAT in the setting of overnutrition (29,39,72), raising the possibility that Ad-FGF21 could be a source of circulating FGF21 in this context.…”
Section: Overfeeding and Obesitymentioning
confidence: 88%
“…Serum FGF21 levels were also significantly elevated in subjects with metabolic syndrome (defined as having 3 or more of the following criteria: central obesity (waist circumference ≥ 80 cm in women and 90 cm in men), hypertriglyceridemia (fasting triglycerides ≥ 1/69 mmol/L), low HDL cholesterol (fasting HDL < 1.29 mmol/L in women and < 1.04 mmol/L in men), hyperglycemia (fasting glucose ≥ 5.6 mmol/L or taking oral hypoglycemic agents for the treatment of type 2 diabetes), or hypertension (sitting blood pressure ≥ 130/85 mmHg) ( 28 ). Plasma FGF21 levels were also measured in a separate cohort of men and women in Mexico (n=241), and also showed a positive correlation between serum FGF21 levels and body weight and waist circumference ( 76 ). Similarly, serum FGF21 positively correlated with BMI, waist circumference, and adiposity in healthy men and those with diabetes in Tanzania ( 77 ).…”
Section: Pathological Conditions Associated With Fgf21mentioning
confidence: 99%
“…FGF21, a hepatokine with a key metabolic role in glucose and lipid homeostasis is also expressed in HIV patients. The detection of a high FGF21 serum level in these patients was associated with MetS, lipodistrophy, and severe steatosis (239)(240)(241). Given the strong correlations between FGF21 and metabolic parameters, FGF21 has been suggested as a possible prognostic marker to monitor HALS and its therapy as well as the ART-associated cardiovascular risk (242).…”
Section: Hepatokine/adipokine Axis Breakdown In Hiv-specific Nafldmentioning
confidence: 99%